Demosthenes and the defense of the sovereignty of the ’polis’ - André, Alessandra (Romanitas - Revista de Estudos Grecolatinos, 2013)
In this article, we will explore the political thought of Demosthenes (384-322 BC) as to the defense of the autonomy of the polis and the action against the Macedonia. We will focus on the three Philippics analysis with the intent to capture in these speeches the sense of Greek identity connected to the polis, a single political system seen by Demosthenes as worthy for the Hellenes and the only one capable of preserving the freedom of Hellas. In return, we will examine how, at the same time, Demosthenes, when speaking of being Greek, the nature of the polis, builds an entire rhetoric according to which Philip II, king of Macedonia, is symbolized as a barbaric enemy of Hellas.